PENEGAKAN HUKUM TERHADAP INFLUENCER YANG MENGIKLANKAN PRODUK KOSMETIK ILEGAL PADA PLATFORM MEDIA SOSIAL INSTAGRAM DI WILAYAH KEPOLISIAN RESOR KOTA PEKANBARU - Ela Aprida Nafliana (Lafadz Jaya Publisher, 2023)
This study aims to determine Law Enforcement Against Influencers Advertising Illegal Cosmetic Products on the Instagram Social Media Platform in the Pekanbaru City Police Legal Area and To Know the Ideal Concept of Law Enforcement Regulations Against Influencers Advertising Illegal Cosmetic Products on Instagram Social Media Platforms in the Resort Police Legal Area Pekanbaru City. This research is a type of juridical sociological research, namely empirical research to find theories about the process of occurrence and about the working process of law in society. The approach method used in this study uses a problem approach which is carried out in a juridical-empirical manner, namely a juridical approach is used to analyze various laws related to the problems that the author raises above, while an empirical approach is used to analyze law by looking at the legal reality that occurs in public. Empirical juridical is also called sociological juridical.